Multidisciplinary Management of a Rare Case of a Huge LowGrade Chondrosarcoma of the Lumbar Spine: A Case Report - Samuel Jason Rolando Tua; Hendy Rachmat Primana; Agus Hadian Rahim; Ahmad Ramdan; Herry Herman (Indonesian Journal of Cancer, 2020)
Introduction: Chondrosarcoma is the second most common primary bone sarcoma and arising in the spine. It is estimated to be 2% to 12% in incidence from various series. The use of neoadjuvant and adjuvant chemotherapy for chondrosarcomas is controversial. Low- and intermediate-grade chondrosarcomas respond poorly to chemotherapy. Although not much data on the efficacy of chemotherapy in the treatment of high-grade chondrosarcomas, it should be considered in any young patient with a high-grade tumor. Radiation is recommended when anything other than wide excision is performed for chondrosarcoma of any grade.Case Presentation: A 24-year old female presented to the clinic with a chief complaint of persistent low back pain and a lump in her back. Initially, the lump was the size of a tennis ball three years ago. At the time of the examination, the lump was at the size of a volleyball about 65 x 63 x 58 centimeters. Systemic and general examinations were unremarkable. There were no comorbid conditions. From the results of the Clinicopathological Conference conducted by neurologists, pathologists, radiologists, orthopedic spine and oncology surgeons, it is advisable to conduct investigations such as x-rays, CT scans, MRI, biopsy, and surgery is recommended for evaluation of expansion of chondrosarcoma, evolving the spinal cord, and for resection of tumors.Conclusion: Early diagnosis and complete resection of tumor and treatment of relevant symptoms represent a viable treatment for this rare disorder to achieve increased life expectancy, low recurrence of tumor, and improvement of quality of life.